Mucosal Associated Invariant T Cells Were Activated and Polarized Toward Th17 in Chronic Obstructive Pulmonary Disease - Qiu, Wenjia; Kang, Ning; Wu, Yanxu; Cai, Yongjun; Xiao, Li; Ge, Haiyan; Zhu, Huili (Frontiers in Immunology, 2021)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease characterized by airway limitation accompanied with infiltration of inflammatory cells. Mucosal associated invariant T (MAIT) cells can recognize bacteria and play an important role in controlling host immune responses by producing cytokines. In this study, we characterized biological function and the ability to secrete cytokines of MAIT cells measured by flow cytometry. Compared to healthy individuals, fewer percentage of MAIT cells had the capacity to produce more IL-17 with the reduction of IFN-γ in COPD patients. We found that HLA-DR expression levels reflected the degree of inflammation and the proportion of IL-17 was significantly correlated with lung function in peripheral blood. In addition, we analyzed that MAIT cells were highly expressed in the lung, and the increased expression of chemokines indicated that MAIT cells had the potential to migrate to inflammatory tissues. This evidence implies that MAIT cells may play a protective role in COPD immunopathology.